Mechanical Performance of rPET Filament Obtained by Thermal Drawing for FFF Additive Manufacturing - Pedro Pires; Martim Lima de Aguiar; André Costa Vieira (Journal of Manufacturing and Materials Processing)
The growing production of plastic waste and its recycling, from a circular economy perspective, faces challenges in finding solutions that are easy to implement, cheap in labor and energy during recycling, and locally implementable to avoid transportation. This work developed and validated a methodology to address these challenges. Designed for small-scale use at home or in schools following a Do It Yourself (DIY) approach, it transforms water bottles into plastic strips, which, after passing through an extruder nozzle, become filaments with a diameter of 1.75 mm. These can replace commercially available thermoplastic filaments. Specimens produced by additive manufacturing with recycled PET (rPET) and commercial PETG showed similar mechanical properties and can serve as alternatives to commercial PETG. PETG shows higher strength (30 MPa) compared to rPET (24 MPa), a slightly higher Young’s modulus of 1.44 GPa versus 1.43 GPa, and greater strain at failure with 0.03 mm/mm against 0.02 mm/mm, making it stiffer and more ductile. This simple and widely applicable local solution may absorb a considerable amount of bottle waste, offering an economical, sustainable alternative to commercial filaments.